Adversity Quotient: Nursing Students - Saetew, Papasinee; Leeyutthanont, Matthawan; Waichompu, Navarat (Journal of The Royal Thai Army Nurses, 2021)
This article aims to present conceptual framework, principles and theories about Adversity Quotient: of nursing students. by presenting the following issues: 1) Concepts and theories of Adversity Quotient, 2) The concept of youth change theory, 3) Contextual concepts of nursing students, and 4) Adversity Quotient of nursing students. It will be based on the CORE conceptual framework to guide students and faculty involved in the application to promote coping and to effectively overcome the obstacles of nursing students.